The Taiga project. Issue 3 (January 2016) - Yashin, I I; Astapov, I I; Barbashina, N S; Bogdanov, A G; Boreyko, V; Budnev, N M; Büker, M; Bruckner, M; Chiavassa, A; Chvalaev, O B; Gafarov, A V; Gorbunov, N; et al.
Abstract: The TAIGA project is aimed at solving the fundamental problems of gamma-ray astronomy and physics of ultrahigh energy cosmic rays with the help of the complex of detectors, located in the Tunka valley (Siberia, Russia). TAIGA includes a wide-angle large area Tunka-HiSCORE array, designed to detect gamma-rays of ultrahigh energies in the range 20 - 1000 TeV and charged cosmic rays with energies of 100 TeV - 100 PeV, large area muon detector to improve the rejection of background EAS protons and nuclei and a network of imaging atmospheric Cherenkov telescopes for gamma radiation detection. We discuss the goals and objectives of the complex features of each detector and the results obtained in the first stage of the HiSCORE installation.